Analisis Collaborative Government dalam Meningkatkan Pemulihan Ekonomi Masyarakat di Kabupaten Sumbawa - Ulfriandi Setiawan; Ghenta Geatovan; Muhammad Kamil (Jurnal Ilmu Pemerintahan, 2025)
This study aims to examine and at the same time find out how the Collaborative Government Analysis in Improving Community Economic Recovery during the Pandemic Period. The focus of this research is Sumbawa Regency as the object of its study. This research is a structured literature review with data sources obtained through several reading sources such as journals, mass media and online media. In increasing the economic recovery of the community during the Covid - 19 Pandemic, it will certainly require collaboration from the Government (Collaborative Government). Where Collaborative Governance is one solution of a rigid bureaucracy and is not in the recovery of socio-economic conditions in the new normal era. So the Sumbawa Regency government as a policy maker provides an innovation in improving the economic recovery of the community during the Covid-19 pandemic with the Sumbawa Regency Government Policy in Improving Community Economic Recovery through MSMEs (Micro, Small and Medium Enterprises), such as the first seven PEN programs, JPS ( Social Safety Net), secondly there is business capital assistance for 20 Ultra Micro entrepreneurs (UMI), third is facilitated by licensing subsidies for KUMKM, fourth facilitates halal certification, fifth is assistance from micro business actors (BPUM) or presidential assistance (Banpres), sixth is empowerment UMKM, then the last one is the economic stimulus program. And also with the use of digital technology, these SMEs can reach a wider market, cutting costs. As well as the emergence of many UMKM digital marketing platforms to support the process and performance of these MSMEs because it is seen from the development and development in the form of this infrastructure, of course, public access to develop their business through a digital system is expected to run well.